Development of Technical Skills: Education, Simulation, and Maintenance of Certification. Issue 8 (November 2015) - Sullivan, Sarah A.; Anderson, Barbara M.H.; Pugh, Carla M.
Abstract : Abstract: The goal of this article is to provide a focused overview of technical skills education inside the operating room (OR), opportunities for learning outside of the OR (with a focus on simulation), and methods for measuring technical skills. In addition, the authors review the role of maintenance of certification in continuing education and quality improvement and consider the role that simulation plays in this process. The perspectives on teaching in the OR of both residents and faculty going into the case affect the learning environment, and preoperative interactions between attendings and residents to establish learning needs and goals are important. Furthermore, in regards to attending surgeons improving their skills, interaction with more experienced peers and feedback during and after a procedure can be beneficial. Simulation is increasingly being utilized as an education tool outside of the OR. Training in plastic surgery is poised to exploit simulation in multiple technical areas. There is potential to utilize these simulation environments to collect real-time data, such as motion, visual focus, and pressure. How to incorporate technical skill evaluation results in ways that are most beneficial for learning should be the focus of future research and curriculum development. Finally, simulation could be better utilized as a mechanism for both self and peer evaluation and assessment for continuing education and quality improvement. Professional development for faculty and surgery trainees on how to engage with simulation for teaching and learning and how to translate these experiences into improving patient care will be required.